Towards Post-Transitional Justice - Sri Lestari Wahyuningroem (Jember University Press, 2019)
When democratization took place in 1998 after three decades of authoritarianism in Indonesia, transitional justice became one of the agendas for the country. With the nature of compromised political transition, transitional justice brought together the interest of the elements who wished to challenge the repressive regime, and those who wished to distant themselves from the old regime in order to return to politics. As the result, transitional justice measures were successfully adopted in the beginning of political transition but failed to achieve its goals to break with the old regime and bring justice to victims. Today, after twenty years since reformasi, elements of the politics are consolidated, including those coming from the old regime. Transitional justice is undergoing a period I refer as “post transitional justice”. The main character of this state is the extensive roles of civil society. I argue in this paper that civil society, in particular the human rights groups, have important roles since the beginning of the transition in setting the agenda for transitional justice until today when state-centered mechanisms failed and led to post-transitional justice situation. These groups shift strategies to work from below and from the margins, which give strong character for post-transitional justice in Indonesia.